2004
DOI: 10.1111/j.1651-2227.2004.tb02996.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep patterns in children and adolescents with functional recurrent abdominal pain: objective versus subjective assessment

Abstract: This study of a small group of children and adolescents with functional RAP provides objective evidence that their sleep patterns do not differ from those of normal peers, despite their subjective complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…However, research on sleep in children with chronic abdominal pain, specifically, is limited. A few studies have found that children with abdominal pain self-report higher levels of sleep disturbance than healthy controls, particularly in the areas of sleep onset/maintenance and excessive daytime sleepiness [8,9]. Consistent with this, studies have estimated the prevalence of poor sleep at 25-30% for adults with FGIDs [10-13].…”
Section: Introductionmentioning
confidence: 95%
“…However, research on sleep in children with chronic abdominal pain, specifically, is limited. A few studies have found that children with abdominal pain self-report higher levels of sleep disturbance than healthy controls, particularly in the areas of sleep onset/maintenance and excessive daytime sleepiness [8,9]. Consistent with this, studies have estimated the prevalence of poor sleep at 25-30% for adults with FGIDs [10-13].…”
Section: Introductionmentioning
confidence: 95%
“…Findings on objectively measured sleep are equivocal. While some research shows adolescents with chronic pain have lower sleep efficiency compared to healthy adolescents 20, other findings indicate similar sleep latency, efficiency, and duration 8.…”
Section: Introductionmentioning
confidence: 97%
“…Chronic pain is reported in 20–40% of youth 22, with the majority reporting sleep disturbances 9, 25 including shorter sleep duration 21, 28, poorer sleep quality 8, 20, and more night wakings 13, 36. Disturbed sleep in youth with chronic pain is associated with limitations in social functioning 9, lower quality of life, and greater disability 12, 18.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recent findings have demonstrated that these children and adolescents experience difficulty falling asleep, frequent night awakenings, early morning awakening, and excessive daytime sleepiness. For example, research with subjective and objective sleep measures has documented more nightly arousals and awakenings per hour, higher levels of sleep anxiety, and more daytime sleepiness in children with JRA compared to healthy children, 1,22 and that pain was positively correlated with their reports of sleep disturbances.…”
mentioning
confidence: 99%
“…For example, in a recent study that compared objective to subjective assessment of sleep patterns in children and adolescents with recurrent abdominal pain, the authors found that objective sleep patterns were similar to a healthy control group, whereas subjective reports of sleep were different. 8 Moreover, our study was limited by use of adolescent self-report for all outcome measures, and because of shared method variance, it might have increased the likelihood of finding significant relationships among pain, sleep disturbances, and functional limitations. Third, the correlational design also prohibits conclusions concerning the direction of effects.…”
mentioning
confidence: 99%